A simpler alternative to metal welded double needle single cannula system for TMJ arthocentesis - Reshma H; Kiran H; Puja Londhe (Elsevier, 2022)
We describe a simpler technique of using double needle with single cannula for TMJ arthrocentesis. This technique allows for the numerous benefits for lavage of superior joint space over traditional technique including lower cost, simpler form and same efficacy.